The Effect Of Self Efficacy And Locus Of Control On Student Enterprise Interest - Syauqia, Rafiqah; Siregar, Onan Marakali (Jurnal Sosial Sains dan Komunikasi, 2023)
Slowing economic growth increased the number of unemployed. One solution to this problem is to create new jobs through entrepreneurship. Education should be able to play a role in increasing the number of entrepreneurs in Indonesia. However, the low interest of students in entrepreneurship tends to make students educated, but unemployed after graduating from college. Creating graduates who have knowledge, interest, and entrepreneurial spirit is an important responsibility for universities. This study aims to analyze how the influence of self-efficacy and locus of control on entrepreneurial interest in North Sumatra University students. This study uses a quantitative method involving 100 respondents as the research sample. Sampling was done through a purposive sampling technique. Collecting data using a questionnaire distributed to respondents via google form. The methods used for data analysis are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the variables of self-efficacy and locus of control significantly and simultaneously affect the interest in entrepreneurship. The influence given by the variable self-efficacy and locus of control contributed 17.4% to the variable interest in entrepreneurship.